Pokémon. Sun & Moon. 7 - Kusaka, Hidenori; Turnage, Bryant (VIZ Media, LLC, 2020)
Sun and Moon are brought together one day, and when their paths cross with Team Skull, they'll never be the same. Sun's main goal is making money, and Moon hopes for scientific discoveries. International Police Officers Looker and Anabel hire Sun to follow the mysterious Ultra Beasts as they attack one island after another in the Aloha region. And that's all before a group of Crabrawler steals Sun's special berry for Tapu Fini. All of this leads to the uncovering of Anabel's secret origin.